Association of Motor Abilities and Morphological Characteristics with Results on a Rowing Ergometer - Tomislav Sablic; Sime Versic; Ognjen Uljevic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
This study aimed to determine the association of morphological characteristics and motor abilities on the results achieved on a rowing ergometer. The participants were 36 students of Faculty of Kinesiology of the University of Split, Croatia (21 males, 15 females). The sample of variables consisted of a total of 22 variables: 11 variables measuring morphological characteristics, 10 motor abilities (predictors), and the result on a rowing ergometer. The ergometer variable represented the test result achieved on a rowing ergometer at a distance of 2000 meters. The correlation between predictors and criterion was evidenced by Pearson's product-moment correlation. A big correlation was found between rowing 2000 m on an ergometer and wall squat, stand and reach, body height, foot-tapping and calf skinfold for men; and body height and mass, calf- and mid-upper-arm-circumference, biceps-, triceps-, subscapular- and calfskinfold, medicine ball throw and wall squat test, for women. Success in rowing is directly dependent on morphological characteristics and motor abilities. For more detailed analysis, partial influences of each factor, psychophysical characteristics, technical and tactical abilities and external influence should be taken into consideration.